Isolation and characterization of mutants corresponding to the MENA, MENB, MENC and MENE enzymatic steps of 5′‐monohydroxyphylloquinone biosynthesis in Chlamydomonas reinhardtii. (5th December 2016) - Emonds‐Alt, Barbara; Coosemans, Nadine; Gerards, Thomas; Remacle, Claire; Cardol, Pierre
Significance Statement: Phylloquinone is an essential electron carrier in photosystem I, but the entire biosynthetic pathway in Chlamydomonas was not known. Here we took advantage of the photosynthetic deficiency of a mend mutant to isolate new mutants in this pathway. Summary: Phylloquinone (PhQ), or vitamin K1, is an essential electron carrier (A1 ) in photosystem I (PSI). In the green alga Chlamydomonas reinhardtii, which is a model organism for the study of photosynthesis, a detailed characterization of the pathway is missing with only one mutant deficient for MEND having been analyzed. We took advantage of the fact that a double reduction of plastoquinone occurs in anoxia in the A1 site in the mend mutant, interrupting photosynthetic electron transfer, to isolate four new phylloquinone‐deficient mutants impaired in MENA, MENB, MENC ( PHYLLO ) and MENE . Compared with the wild type and complemented strains for MENB and MENE, the four men mutants grow slowly in low light and are sensitive to high light. When grown in low light they show a reduced photosynthetic electron transfer due to a specific decrease of PSI. Upon exposure to high light for a few hours, PSI becomes almost completely inactive, which leads in turn to lack of phototrophic growth. Loss of PhQ also fully prevents reactivation of photosynthesis after dark anoxia acclimation. In silico analyses allowed us to propose a PhQ biosynthesis pathway in Chlamydomonas that involves 11 enzymatic steps from chorismate located in the chloroplast and in the peroxisome.